How I diagnose and treat myeloid/lymphoid neoplasms with tyrosine kinase gene fusions: how I treat series : myeloproliferative neoplasms - Reiter, Andreas; Metzgeroth, Georgia; Cross, Nicholas C. P. (Blood, 2025)
The fifth edition of the World Health Organization (WHO) classification and the International Consensus Classification (ICC) both include a category "myeloid/lymphoid neoplasms (MLN) with eosinophilia (eo) and tyrosine kinase (TK) gene fusions” (WHO, MLN-TK; ICC, M/LN-eo-TK). This rare group comprises phenotypically and prognostically heterogeneous disorders, which present a significant diagnostic challenge. The rapid and reliable identification of patients with MLN-TK may be delayed due to genetic complexity and significant phenotypic differences, including the chronic phase and primary/secondary blast phase (BP) of myeloid, lymphoid, or mixed phenotype in the bone marrow (BP-BM) and/or at extramedullary sites (extramedullary disease [EMD]). As a result, the entire armamentarium of conventional molecular genetic and cytogenetic techniques complemented by modern sequencing technologies, such as RNA sequencing or whole-genome sequencing, are often required to identify an underlying TK fusion. TK inhibitors (TKIs) with variable efficacy are available for all fusion genes, but a long-term favorable clinical course under TKI monotherapy is currently only observed in MLN-PDGFRA/PDGFRB fusion genes on imatinib. Because primary/secondary BP-BM/EMD occurs more frequently in MLN-FGFR1/JAK2/FLT3/ETV6::ABL1, a sequential combination of selective TKIs with or without prior intensive chemotherapy, rarely local radiotherapy, and/or subsequent allogeneic hematopoietic cell transplantation should be considered.
Online verfügbar: 26. Jul 2024, Artikelversion: 17. April 2025
Gesehen am 24.06.2025